Great world religions Judaism - Gafni, Isaiah M.; Teaching Company (Chantilly, Virginia The Teaching Company, 2003)
Surveys the history, traditions, and practice of Judaism from biblical times to today, with explanations of the major aspects of Jewish culture. Focuses on Judaism from within and how it is understood by its adherents, past and present. Covers topics such as the sacred books of Judaism, modes of worship, the calendar and holidays, and rites of passage such as bar and bat mitzva and marriage. Illustrates how Judaism reinvented itself by embracing the rabbinical tradition after the destruction of the Second Temple in 70 C.E. and considers the thinking of philosophers such as Maimonides.
Lecture 1. What is Judaism? -- Lecture 2. The stages of history -- Lecture 3. The Jewish library -- Lecture 4. The emergence of Rabbinic Judaism -- Lecture 5. Jewish worship, prayer and the synagogue -- Lecture 6. The calendar, a communal life-cycle -- Lecture 7. Individual life-cycles -- Lecture 8. God and man, God and community -- Lecture 9. Philosophers and mystics -- Lecture 10. The legal frameworks of Judaism, Halakha -- Lecture 11. Common Judaism, or a plurality of Judaisms? -- Lecture 12. Judaism and "others."
Lecture transcript and course guidebook published to accompany DVD and and videotapes with the same title.
Includes bibliographical references.
Keywords: Judaism; Judaism -- Study and teaching